Antidiabetic Activity of Caulerpa racemosa: Role of Proinflammatory Mediators, Oxidative Stress, and Other Biomarkers - Mandlik, Rahul V.; Naik, Suresh R.; Zine, Sandip; Ved, Hemen; Doshi, Gaurav (Planta Medica International Open, 2022)
A marine alga, Caulerpa racemose (seaweed), exhibits few biological activities, such as antinociceptive/anti-inflammatory, antitumor, and growth regulator. This study aimed to determine the antidiabetic activity of this seaweed. High-performance thin-layer chromatography of C. racemosa ethanolic extract was performed to identify its active constituents. Antidiabetic activity of C. racemosa ethanolic extract (100 and 200 mg/kg) was evaluated using various biochemical paradigms against glipizide (5 mg/kg) in a streptozotocin-induced diabetes rat model. High-performance thin-layer chromatography revealed β-sitosterol as an active constituent and also indicated the presence of saponins and alkaloids. Treatment with C. racemosa ethanolic extract significantly reduced blood glucose levels in diabetic rats, and the degree of glucose reduction was comparable to that attained by glipizide treatment. The C. racemosa ethanolic extract treatment restored the impaired glycosylated hemoglobin level, liver glycogen level, glucose uptake by hemidiaphragm, and glucose transport by hepatic cells. Pretreatment with C. racemosa ethanolic extract also restored lipid abnormalities, elevated liver enzymes, elevated inflammatory markers, and depleted endogenous antioxidants. A superior effect was shown by C. racemosa ethanolic extract (200 mg/kg) over glipizide (5 mg/kg). Moreover, the restoration of the histoarchitecture of the pancreas by C. racemosa ethanolic extract (200 mg/kg) was comparable to that of the glipizide (5 mg/kg) treatment group. The present experimental findings demonstrate significant antidiabetic activity of C. racemosa ethanolic extract in diabetic rats using various biochemical paradigms. Further, C. racemosa ethanolic extract seems to be safe and does not affect vital organs adversely.
Keywords: seaweed; Caulerpa racemosa; Caulerpaceae; type 2 diabetes mellitus; antioxidant; anti-inflammatory